HUBUNGAN ANTARA KETELADANAN GURU PAI TERHADAP TINGKAT PEMAHAMAN NILAI-NILAI AKHLAK PADA SISWA SMP NEGERI 1 JATI AGUNG - NUZULI QURNIA ARASI; UMI HIJRIYAH; DEDY IRAWAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated The significance of Islamic Religious Education (PAI) instructors' outstanding role in forming students' moral ideals served as the impetus. In addition to providing instructional materials, PAI teachers also act as role models for students everyday conduct. The purpose of this study was to investigate the relationship between PAI teachers' exemplary roles and students' moral value knowledge at SMP Negeri 1 Jati Agung. This study took a quantitative approach with a correlational research methodology. The sample consisted of 28 people. Data were acquired via surveys and paperwork. Data was analyzed using normality tests, homogeneity tests, and Spearman Rank correlation with the use of SPSS software. The results showed that the PAI teacher exemplary variable was normally distributed with a significance value of 0.167 (>0.05), while the moral values understanding variable was not normally distributed with a significance value of <0.001 (<0.05). The homogeneity test showed a significance value of 0.163 (>0.05). The Spearman Rank correlation test produced a correlation coefficient of -0.105 with a significance value of 0.596 (>0.05), indicating no significant relationship between the exemplary role of PAI teachers and students’ understanding of moral values.